Post a New Question


posted by .

solve (-2y)^2(3x^3)

I totally don't get this problem. Does my answer come out with x and y ? how do I eliminate?

  • math -

    I don't get it either, since there is nothing to "solve".

    "Solving" requires an equation.

    if you wanted to simplify it , it would be
    = 12 x^3 y^2

  • math -

    =(-2)^2 y^1 * (3x^3)

    = 4(3)y^2 x^3

    =12y^2 x^3

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question